Investigating the Extent of Primer Dropout in SARS-CoV-2 Genome Sequences During the Early Circulation of Delta Variants - Borcard, Loïc; Gempeler, Sonja; Terrazos Miani, Miguel A.; Baumann, Christian; Grädel, Carole; Dijkman, Ronald; Suter-Riniker, Franziska; Leib, Stephen L.; Bittel, Pascal; Neuenschwander, Stefan; Ramette, Alban (Frontiers in Virology, 2022)
The SARS-CoV-2 Delta variant, corresponding to the Pangolin lineage B.1.617.2, was first detected in India in July 2020 and rapidly became dominant worldwide. The ARTIC v3 protocol for SARS-CoV-2 whole-genome sequencing, which relies on a large number of PCR primers, was among the first available early in the pandemic, but may be prone to coverage dropouts that result in incomplete genome sequences. A new set of primers (v4) was designed to circumvent this issue in June 2021. In this study, we investigated whether the sequencing community adopted the new sets of primers, especially in the context of the spread of the Delta lineage, in July 2021. Because information about protocols from individual laboratories is generally difficult to obtain, the aims of the study were to identify whether large USRs were present in deposited Delta variant genome sequences (from April to August 2021), to investigate the extent of the coverage dropout among all the currently available Delta sequences in six countries, and to propose simple PCR primer modifications to sequence the missing region, especially for the first circulating Delta variants observed in 2021 in Switzerland. Candidate primers were tested on few clinical samples, highlighting the need to further pursue primer optimization and validation on a larger and diverse set of samples.